If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -26 = -6 + 3x Reorder the terms: -26 + 8x = -6 + 3x Solving -26 + 8x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -26 + 8x + -3x = -6 + 3x + -3x Combine like terms: 8x + -3x = 5x -26 + 5x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 -26 + 5x = -6 + 0 -26 + 5x = -6 Add '26' to each side of the equation. -26 + 26 + 5x = -6 + 26 Combine like terms: -26 + 26 = 0 0 + 5x = -6 + 26 5x = -6 + 26 Combine like terms: -6 + 26 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| 1=8(a+8)+1 | | 48=-8a | | x^2+30=13x | | 219-4x=32x+23 | | 7x+6(5x-15)=169 | | -14+13x=5 | | x^2-12x+36=40 | | 4x-3-8x+1=-5x+9 | | 3b+4.4=6.2-3c | | 7w-6w+1=10-4 | | 10h+25=3h-3 | | -(5+6x)=13 | | 4x^2-80x=0 | | -21-11x=15 | | .25(20+4s)-.5(12+2s)= | | x^2+18x+81=50 | | -111-9x=10x+22 | | 3x^3+9x^2+4x+12=0 | | 2x+3x+11=101 | | (r-2t)(r+4w)= | | 5b-2(3b+1)=1 | | 4x-12=60 | | 0.11x+0.8(x-4)=0.01(2x-1) | | Mx+2a=.333(c-x) | | x^2+2x+1=42 | | x^2+12x+36=-25 | | 0.2x+3.1=-5.3 | | 19-5a=16 | | -9(s+5)-9(s-7)= | | 3x+4+10= | | x+2x=21 | | 7(5b-8)= |